My Math Forum partial fraction decomposition
 User Name Remember Me? Password

 Pre-Calculus Pre-Calculus Math Forum

 October 29th, 2017, 07:08 PM #1 Newbie   Joined: Oct 2017 From: cali Posts: 8 Thanks: 0 partial fraction decomposition My issue with this problem is that after factoring out an x, i get x^2-x+4 which gives me x(x^2-x+4). Normally i would factor it out but i can't do it normally, using quadratic equations which i was told not to do in class. Solving for a is easy enough, as i make x = 0 to cancel out B and C so i can solve for A. But after that i'm pretty lost. Here's a image of the work in class we did above.
 October 29th, 2017, 07:29 PM #2 Senior Member     Joined: Sep 2015 From: USA Posts: 2,264 Thanks: 1198 you've got it all solved $A=\dfrac 1 2,~B=-\dfrac 1 2,~C=\dfrac 3 2$ $\dfrac{x+2}{x^3-x^2+4x} =\dfrac 1 {2x} + \dfrac{-x+3}{2(x^2-x+4)}$
October 29th, 2017, 08:44 PM   #3
Newbie

Joined: Oct 2017
From: cali

Posts: 8
Thanks: 0

Quote:
 Originally Posted by romsek you've got it all solved $A=\dfrac 1 2,~B=-\dfrac 1 2,~C=\dfrac 3 2$ $\dfrac{x+2}{x^3-x^2+4x} =\dfrac 1 {2x} + \dfrac{-x+3}{2(x^2-x+4)}$
my apologies, didn't make it clear what i was struggling with. We finished it in class but im' not sure how solving for b and c for example works. I don't know the steps necessary to approach problems like that.

October 30th, 2017, 12:07 AM   #4
Senior Member

Joined: Sep 2015
From: USA

Posts: 2,264
Thanks: 1198

Quote:
 Originally Posted by materialartist09 my apologies, didn't make it clear what i was struggling with. We finished it in class but im' not sure how solving for b and c for example works. I don't know the steps necessary to approach problems like that.
ok we'll start it from scratch

$f(x) = \dfrac{x+2}{x(x^2-x+4)}$

$x^2-x+4 \text{ cannot be factored further.}$

we set it up as usual

$f(x) = \dfrac{A}{x} + \dfrac{Bx + C}{x^2-x+4}$

$\dfrac{x+2}{x(x^2-x+4)} = \dfrac{A(x^2-x+4) + Bx^2 + Cx}{x(x^2-x+4)} = \dfrac{(A+B)x^2+(-A+C)x + 4A}{x(x^2-x+4)}$

now we just match up the coefficients of the powers of $x$

$x^2:~~0 = A+B$

$x: ~~1 = -A + C$

$1:~~2=4A$

solving these

$A = \dfrac 1 2$

$C = 1+\dfrac 1 2 = \dfrac 3 2$

$B=-A = -\dfrac 1 2$

so

$\dfrac{x+2}{x(x^2-x+4)} = \dfrac{1}{2x} + \dfrac{3-x}{2(x^2-x+4)}$

 November 5th, 2017, 03:56 AM #5 Math Team   Joined: Jan 2015 From: Alabama Posts: 3,261 Thanks: 895 Another way: Once you have $\displaystyle \frac{x+ 2}{x(x^2- x+ 4)}= \frac{A}{x}+ \frac{Bx+ C}{x^2- x+ 4}$, multiply both sides by $\displaystyle x(x^2- x+ 4)$ to clear the fractions and get $\displaystyle x+ 2= A(x^2- x+ 4)+ x(Bx+ C)$ which must be true for all x. In particular, taking x equal to three different values gives three different values gives three different equations to solve for A, B, and C. Letting x= 0, $\displaystyle 2= 4A$ so $\displaystyle A= \frac{1}{2}$. Letting x= 1, $\displaystyle 3= 4A+ B+ C= 2+ B+ C$ so $\displaystyle B+ C= 1$. Letting x= -1, $\displaystyle 1= 6A- (- B+ C)= 3+ B- C$ so $\displaystyle B- C= -2$. Adding those two equations, $\displaystyle 2B= -1$ so $\displaystyle B= -\frac{1}{2}$ and then [math]C= \frac{3}{2}. $\displaystyle \frac{x+ 2}{x(x^2- x+ 4)}= \frac{1}{2x}+ \frac{3- x}{2(x^2- x+ 4)}$ as before. Last edited by Country Boy; November 5th, 2017 at 03:59 AM.

 Tags decomposition, fraction, partial

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post WWRtelescoping Complex Analysis 4 April 27th, 2014 05:44 PM strawberryPK Calculus 1 February 9th, 2011 09:10 PM RMG46 Algebra 16 July 5th, 2010 08:26 PM mathman2 Calculus 2 February 14th, 2010 06:21 AM mnangagwa Calculus 3 March 20th, 2009 10:43 PM

 Contact - Home - Forums - Cryptocurrency Forum - Top